How can we improve adherence to exercise programs in patients with osteoarthritis?: A randomized controlled trial [Di̇z osteoartri̇ti̇ olan hastalarin egzersi̇z programlarina uyumlari nasil artirabi̇li̇ri̇z?: Randomi̇ze kontrollü çalişma] - (:unkn) unknown (My University, 2012)
Introduction: To test the efficacy of a method which can improve compliance of osteoarthtritis patients to exercise treatment. Materials and Method: This is a randomized controlled, intervention study. Sixty-four patients who applied to the Family Medicine outpatient clinic of Marmara University Hospital were enrolled. Half of the paticipants were allocated randomly to the intervention group(IG) and the other half to the control group (CG). The study period was 12 weeks. IG was given leaflets and gradual exercise training by demonstration. CG received leaflet about exercises. We assessed participitans' adherence with patients' diaries and telephone contact. We determined WOMAC scores of the participants at each follow-up visit. Results: Of the participants 98.4% were women. Mean age was 56.8±9.27 in the IG and 52.4±10.0 in the SCG. Adherence to exercise in the IG was high (median 100%). Pain and WOMAC scores improved significantly [chronologically 43.5 (25.7-50.25), 18.5 (10.5-27.75), 16.5 (9.0-25.0), 9.5 (5.0-18.0)(p=0.0001)]. Although exercise adherence of the SCG was good initially, long-term adherence was only moderate (respectively 72.5 (55.0-97.5) and 55 (25.0-85.0)(p=0.036). Improvement of pain and WOMAC score in the SCG was lower than the IG [respectively 36.0 (23.5-42.25), 31.5 (21.25-46.25), 27.0 (15.25-39.0)(p=0.037)]. Conclusion: Gradual exercise education with demonstration might improve adherence.
Keywords: Counseling; Exercise Therapy; Patient Compliance; Patient Education as Topic